Benefits of caloric restriction in the myenteric neuronal plasticity in aging rats - PEREIRA,JOICE N.B. (2014)
Aging is a biologic process characterized by progressive damage of structures and functions of organic systems. In gastrointestinal tract, it can involve enteric nervous system, which plays an important role in digestion and absorption of nutrients, causing hastening of intestinal transit thus reducing its absorptive function. Caloric restriction has been used in several studies with the intention of delaying deleterious effects of aging. This study aimed to evaluate the effects of caloric restriction on myenteric neurons of ileum by aging in rats. 30 Wistar rats were grouped as follows: GI (animals aged 6 months fed with normal diet), GII (animals aged 18 months fed with normal diet) and GIII (animals aged 18 months subject to 31% of caloric restriction). The rats of the GI group were euthanized at 6 months of age and after experimental period of 12 months animals of the group GII and GIII were euthanized, the ileum of all groups were collected, measured and processed by NADPH-dp and Acetylcholinesterase. Quantitative analysis of neurons revealed that aging promotes the increasing of myenteric neurons NADPH-dp and reduces Acetylcholinesterase neuronal population. However, in the cellular profile area, were not observed significant differences between the groups. The caloric restriction has been efficient and can be used preventively because it minimizes quantitative changes associated with aging on ileum myenteric plexuses.